Development and Psychometric Properties of Environmental, Social, and Governance (ESG) Standards Perceived by Workers, Managers, and Executives - Ajayi, Oluseyi; Fakunmoju, Sunday (Technium Business and Management, 2024)
Purpose: Environmental, social, and governance (ESG) benchmarks, introduced in the early 2000s as a complement to corporate social responsibility (CSR), assess the environmental sustainability, societal impact, and ethical responsibility of organizational operations. Despite the growing importance of ESG and the development of various financial metrics, there remains a shortage of empirically validated scales to measure stakeholders' perceptions of these benchmarks. This study aims to develop and validate the ESG-Perception scale, focusing on internal stakeholders such as employees, managers, and executives. Method: The study sampled employees/workers (N = 300) with a mean age of 42.44 years (SD = 13.18) and managers and executives (N = 302) with a mean age of 37.93 years (SD = 10.38). There were more female employee/worker participants (n = 163, 54.5%) than male participants (n = 136, 45.5%), while there were more male manager and executive participants (n = 163, 54.2%) than female participants (n = 138, 45.8%). The majority of employees/workers identified as White/Caucasian (61%, n = 183), similar to the majority of managers and executives, who identified as White/Caucasian (62.3%, n = 188). Exploratory factor analysis (EFA) using employee/worker data was conducted to examine the factor structure of ESG-Perception, while confirmatory factor analysis (CFA) models—including single-factor, first-order, and bi-factor models—were used with manager and executive data to validate the scale’s factor structure and dimensionality. Measurement invariance across gender and race was also tested to ensure the equivalence of the factor structure. The study further assessed the scale’s convergent and discriminant validity. Results: The ESG-Perception scale effectively captured internal stakeholders' perceptions of ESG benchmarks. A multidimensional, three-factor structure was identified, which aligned with the data. The factor structure was invariant across gender and race, allowing for comparisons of latent means across these groups. Convergent validity indicated that perceptions of diversity and inclusion, personality, leadership qualities, and styles influenced endorsement of ESG standards. With the exception of the Environmental and Governance constructs in the data for managers and executives, clear discriminant validity was observed for the scale’s constructs, demonstrating their distinct conceptual boundaries. However, the absence of discriminant validity between the Environmental and Governance constructs indicated overlapping conceptual dimensions, which is particularly indicative of industries where governance practices and environmental performance are closely linked. The bifactor models demonstrated both multidimensionality and unidimensionality for the scale. Conclusions: The ESG-Perception scale contributes to the body of knowledge on sustainability, corporate social responsibility, and ethical responsibility. It supports the application of Stakeholder and Upper Echelons theories and provides valuable insights into how internal stakeholders perceive ESG principles. Knowledge derived from its use can enhance ESG advocacy and help organizations develop effective strategies for adopting, implementing, and complying with ESG frameworks. This can promote transparency, sustainability, and improve corporate practices and outcomes. Despite exhibiting both unidimensional and multidimensional characteristics, the choice of whether to treat the scale as unidimensional or multidimensional will depend on the specific research goals and context.